Simple synthesis of 3-acyl-5-alkyl(aryl)isoxazoles from terminal alkynes and nitrates of alkaline metals or ammonium; Central European Journal of Chemistry; Vol. 3, iss. 3 - Rogachev V. O. Victor Olegovich; Filimonov V. D. Viktor Dmitrievich; Kulmanakova J. Yu.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Bender W. (2005, 2005)
A simple and general synthesis of 3-acyl-5-alkyl(axyl)isoxazoles by reaction of terminal alkynes with nitrates in acetic acid in the presence of SO3 or alkaline salts is described.